Interpretability as a dynamic of human-AI interaction - Thieme, Anja; Cutrell, Ed; Morrison, Cecily; Taylor, Alex; Sellen, Abigail (Interactions, 2020)
HCI and UX include translating research findings into design practice and translating knowledge from outside the HCI community into the academicv context. The centerpiece of this inquiry is Dialogues, a new section that will feature in-depth discussions on important topics in HCI, UX, and beyond.